Scientific excellence and extramural research grants: Beggars can't be choosers? - Christoph Grimpe (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
Several reviews and impact assessment studies have concluded that the Sixth Framework Programme for Research and Technological Development (FP6) succeeded in fostering scientific excellence and attracting the 'A Team' in public science. However, these studies typically fail to contrast their findings with the variety of funding opportunities available to public science. Based on a sample of more than 1,000 scientists at universities and public research institutes in Germany, this paper finds that highly credentialed faculty typically chose other funding opportunities than FP6, for example grants from science foundations or industry. In fact, FP6 only seems to be attractive for the scientific 'B Team' that works rather application oriented. The findings further indicate that an FP6 participation substitutes for other grant programmes while the latter are complementary to each other. If this is intended to be changed other funding priorities will be required, for example smaller team sizes, less predefined research topics, a reduced administrative burden, and a higher quality of the peer review system.
Keywords: L13; O31; 330; Research funding; scientist productivity; Sixth Framework Programme; Europäische Forschungs- und Technologiepolitik; Wissenschaftler; Entscheidung; Forschung; Produktivität; Deutschland